Planar pattern reconfigurable antenna with eight switchable beams for WiMax and WLAN applications. Issue 10 (1st July 2016) - Alam, Md Shahidul; Abbosh, Amin
Abstract : A planar pattern reconfigurable antenna designed for IEEE 802.11 b/g standard 2.4 GHz WiMax and WLAN applications is presented. The design is realised using a uniform arrangement of eight switch‐controlled tapered strips symmetrically placed around a central circular disc on the top layer of an FR4 board. The antenna has a compact circular structure with overall diameter of 0.64 λ 0 in the free space for 2.4 GHz. To control the radiation pattern of the antenna, each of the tapered strips is connected to the ground via a PIN diode. Depending on the switching status of the eight PIN diodes, the tapered strips work in grounded or open‐ended mode and thus the antenna offers eight switchable patterns. To validate the design, the antenna is prototyped and its performance is verified in a far‐field anechoic chamber. The simulated and measured results prove the antenna's reconfigurability of the main beam in eight directions with 45° steps in the azimuth plane and a vertical tilting angle of 36°. Over the operating band 2.35–2.61 GHz, the antenna has a stable gain of around 4.5 dBi, and front‐to‐back ratio of more than 18 dB. Compared with recent designs, this antenna is more compact, has larger beam deflection off the boresight and more beam steering states.